It's not easy being green : How chief sustainability officers and their competence affects sustainability reporting - Van Dalen, Levi; Tyll, Ladislav; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This study examines the influence of the Chief Sustainability Officer (CSO) on the extent and quality of sustainability reporting within firms. The quantity of reporting was assessed using a disclosure score that measures the volume of reported data, while the quality was evaluated based on external assurance practices and adherence to Global Reporting Initiative (GRI) standards. This research specifically analysed the impact of the presence of a CSO, the role association with the CEO or CFO, and their competence in sustainability on these reporting metrics. The findings reveal a consistently positive association between CSOs and the adoption of GRI standards. However, the effects on reporting volume and assurance practices showed mixed results, suggesting the presence of CSOs assigned for symbolic reasons. These outcomes underscore the complexity of reasoning behind appointment of CSOs and highlight the need for further research and definition of the ‘symbolic CSO’.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses